2015
DOI: 10.1016/j.psyneuen.2015.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-pituitary-adrenal axis dysregulation and cortisol activity in obesity: A systematic review

Abstract: a b s t r a c tBackground: Although there is substantial evidence of differential hypothalamic-pituitary-adrenal (HPA) axis activity in both generalized and abdominal obesity, consistent trends in obesity-related HPA axis perturbations have yet to be identified. Objectives: To systematically review the existing literature on HPA activity in obesity, identify possible explanations for inconsistencies in the literature, and suggest methodological improvements for future study. Data sources: Included papers used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
203
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(216 citation statements)
references
References 91 publications
(137 reference statements)
10
203
3
Order By: Relevance
“…This may be due to potential opposing effects of early adversity and adiposity on HPA axis functioning. In past studies, early adversity has been associated with decreased HPA activity whereas adiposity has been associated with enhanced HPA activity, though not all studies have observed these relations (Chiang et al, 2015b; Repetti et al, 2011; Rodriguez et al, 2015). Similarly, in the present study, greater exposure to early adversity was associated with decreased total cortisol output and reactivity whereas greater WC was associated with greater HPA reactivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to potential opposing effects of early adversity and adiposity on HPA axis functioning. In past studies, early adversity has been associated with decreased HPA activity whereas adiposity has been associated with enhanced HPA activity, though not all studies have observed these relations (Chiang et al, 2015b; Repetti et al, 2011; Rodriguez et al, 2015). Similarly, in the present study, greater exposure to early adversity was associated with decreased total cortisol output and reactivity whereas greater WC was associated with greater HPA reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Both early adversity and depression have been associated with alterations in the HPA axis, which regulates inflammatory processes (Burke et al, 2005; Chiang et al, 2015b; Repetti et al, 2011; Rohleder, 2014). Furthermore, there is some evidence suggesting HPA functioning is dysregulated in the presence of greater adiposity (Rodriguez et al, 2015). As such, interaction effects between early adversity and depressive symptoms and adiposity may extend to the HPA axis.…”
Section: Introductionmentioning
confidence: 99%
“…Hereby, a general correlation between the BMI and cortisol can be observed [9]. A systematic review of Incollingo Rodriguez et al [10] demonstrated that obese individuals show a greater stress-related cortisol response to laboratory acute challenges. However, the five included studies had methodological differences and limitations [9, 11-14].…”
Section: Introductionmentioning
confidence: 99%
“…The literature, to date, is not conclusive, which could be due to the differential effects of generalized obesity against abdominal obesity or modulators such as sex, sex hormones and chronic stress (Incollingo Rodriguez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%